Waning effectiveness against COVID-19-related hospitalization, severe complications, and mortality with two to three doses of CoronaVac and BNT162b2: a case–control study - Vincent Ka Chun Yan; Eric Yuk Fai Wan; Xuxiao Ye; Anna Hoi Ying Mok; Francisco Tsz Tsun Lai; Celine Sze Ling Chui; Xue Li; Carlos King Ho Wong; Philip Hei Li; Tiantian Ma; Simon Qin; Chak Sing Lau; et al. (Emerging Microbes and Infections)
Background: This study aims to evaluate waning effectiveness against severe and fatal COVID-19 with two to three doses of CoronaVac/BNT162b2, where data are limited. Methods: A case–control study included individuals aged ≥18 years, unvaccinated or received two to three doses of CoronaVac/BNT162b2, using electronic healthcare databases in Hong Kong. Those with first COVID-19-related hospitalization, severe complications, or mortality between 1 January and 15 August 2022 were defined as cases and matched with up-to-10 controls by age, sex, index date, and Charlson Comorbidity Index. Vaccine effectiveness (VE) against COVID-19-related outcomes was estimated at different time intervals from second and third-dose vaccination (0–13 up-to 210–240 days) using conditional logistic regression adjusted for comorbidities and medications. Results: By 211–240 days after second dose, VE against COVID-19-related hospitalization reduced to 46.6% (40.7–51.8%) for BNT162b2 and 36.2% (28.0–43.4%) for CoronaVac, and VE against COVID-19-related mortality were 73.8% (55.9–84.4%) and 76.6% (60.8–86.0%). After third dose, VE against COVID-19-related hospitalization decreased from 91.2% (89.5–92.6%) for BNT162b2 and 76.7% (73.7–79.4%) for CoronaVac at 0–13 days, to 67.1% (60.4–72.6%) and 51.3% (44.2–57.5%) at 91–120 days. VE against COVID-19-related mortality for BNT162b2 remained high from 0–13 days [98.2% (95.0–99.3%)] to 91–120 days [94.6% (77.7–98.7%)], and for CoronaVac reduced from 0–13 days [96.7% (93.2–98.4%)] to 91–120 days [86.4% (73.3–93.1%)]. Conclusions: Significant risk reduction against COVID-19-related hospitalization and mortality after CoronaVac or BNT162b2 vaccination was observed for >240 and >120 days after second and third doses compared to unvaccinated, despite significant waning over time. Timely administration of booster doses could provide higher levels of protection.